2023
DOI: 10.1111/jnc.15785
|View full text |Cite
|
Sign up to set email alerts
|

CDGSH iron sulfur domain 2 over‐expression alleviates neuronal ferroptosis and brain injury by inhibiting lipid peroxidation via AKT/mTOR pathway following intracerebral hemorrhage in mice

Abstract: Ferroptosis has been implicated in the pathogenesis of secondary brain injury following intracerebral hemorrhage (ICH), and regulating this process is considered a potential therapy for alleviating further brain injury. A previous study showed that CDGSH iron sulfur domain 2 (CISD2) can inhibit ferroptosis in cancer. Thus, we investigated the effects of CISD2 on ferroptosis and the mechanisms underlying its neuroprotective role in mice after ICH. CISD2 expression markedly increased after ICH. CISD2 over‐expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…[ 311 ] This observation was corroborated by other studies. [ 306 , 307 , 308 , 309 , 312 , 317 , 318 ] Previous studies have demonstrated that specific regulators of ferroptosis, including CDGSH iron sulfur domain 2 (CISD2), [ 319 ] NOX4, [ 320 ] SRY‐box transcription factor 10 (SOX10), [ 321 ] and forkhead box O3 (FOXO3) [ 322 ] play crucial roles in regulating ferroptosis in secondary brain injury after ICH. Increased CISD2 alleviates brain injury by inhibiting lipid peroxidation and ferroptosis via AKT/mTOR in mice.…”
Section: Ferroptosis In Neurological Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 311 ] This observation was corroborated by other studies. [ 306 , 307 , 308 , 309 , 312 , 317 , 318 ] Previous studies have demonstrated that specific regulators of ferroptosis, including CDGSH iron sulfur domain 2 (CISD2), [ 319 ] NOX4, [ 320 ] SRY‐box transcription factor 10 (SOX10), [ 321 ] and forkhead box O3 (FOXO3) [ 322 ] play crucial roles in regulating ferroptosis in secondary brain injury after ICH. Increased CISD2 alleviates brain injury by inhibiting lipid peroxidation and ferroptosis via AKT/mTOR in mice.…”
Section: Ferroptosis In Neurological Diseasesmentioning
confidence: 99%
“…Increased CISD2 alleviates brain injury by inhibiting lipid peroxidation and ferroptosis via AKT/mTOR in mice. [ 319 ] The transcription factor SOX10 inhibits ferroptosis of hippocampal neurons after ICH through increasing miR‐29a‐3p expression, resulting in suppression of ACSL4 transcription. [ 321 ] Silencing FOXO3 ameliorates post‐ICH brain damage through inhibiting neuronal ferroptosis via down‐regulating NOX4 transcription levels.…”
Section: Ferroptosis In Neurological Diseasesmentioning
confidence: 99%
“…These are: CISD1 or mitoNEET, localized to the outer mitochondrial membrane, CISD2 or NAF-1, localized to the outer endoplasmic reticulum (ER), mitochondria, and ER-mitochondria associated membranes (MAM), and CISD3 or MiNT, localized inside the mitochondria. Although multiple studies have shown that CISD1 and CISD2 are involved in the progression of different human pathologies, including cancer, diabetes, neurodegeneration, obesity, and cardiovascular disease [1][2][3][9][10][11][12][13][14][15][16][17] , as well as the genetic disease Wolfram Syndrome 2 (caused by CISD2 deficiency) [18][19][20] , very little is known about the function of CISD3.…”
Section: Introductionmentioning
confidence: 99%